2013
DOI: 10.3892/ijo.2013.2143
|View full text |Cite
|
Sign up to set email alerts
|

Oleifolioside B-mediated autophagy promotes apoptosis in A549 human non-small cell lung cancer cells

Abstract: The biochemical mechanisms of cell death by oleifolioside B (OB), a cycloartane-type triterpene glycoside isolated from Dendropanax morbifera Leveille, were investigated in A549 human lung carcinoma cells. Our data indicated that exposure to OB led to caspase activation and typical features of apoptosis; however, apoptotic cell death was not prevented by z-VAD-fmk, a pan-caspase inhibitor, demonstrating that OB-induced apoptosis was independent of caspase activation. Subsequently, we found that OB increased au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…No cytotoxic effects of 0-300 µM 1-TD on H. pylori-infected gastric epithelial cells were evident. In contrast, previous studies have demonstrated that oleifolioside A and B, ethanol and methanol extracts isolated from D. morbifera have cytotoxic effects on human leukemia cells (1), lung carcinoma cells (24), cervical carcinoma cells (4) and hepatocellular carcinoma cells (5). Therefore, the results of the present study suggested that the inhibition of H. pylori-induced inflammation in gastric epithelial cells is not due to cell toxicity.…”
Section: Discussioncontrasting
confidence: 94%
“…No cytotoxic effects of 0-300 µM 1-TD on H. pylori-infected gastric epithelial cells were evident. In contrast, previous studies have demonstrated that oleifolioside A and B, ethanol and methanol extracts isolated from D. morbifera have cytotoxic effects on human leukemia cells (1), lung carcinoma cells (24), cervical carcinoma cells (4) and hepatocellular carcinoma cells (5). Therefore, the results of the present study suggested that the inhibition of H. pylori-induced inflammation in gastric epithelial cells is not due to cell toxicity.…”
Section: Discussioncontrasting
confidence: 94%
“…24,25 Moreover, it was reported that PINK1 in conjunction with Parkin could affect mitochondrial integrity in some tissues, such as dopaminergic neurons. 30,31 Moreover, induction of mitochondrial autophagy was reported to serve as an inhibitor of cell proliferation. 27 Similarly, the PINK1/ Parkin-directed pathway was previously linked to mitochondrial damage, ubiquitylation and mitochondrial autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…29 Both mitochondrial autophagy and apoptosis are highly regulated biological processes affecting tissue development and diseases, and a study reported that mitochondrial autophagy induced apoptosis in lung cancer cells. 30,31 Moreover, induction of mitochondrial autophagy was reported to serve as an inhibitor of cell proliferation. 32 Similarly, accumulating evidence has demonstrated that apoptosis is induced in ALI, and inhibition of apoptosis attenuates lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids are a group of naturally occurring chemical 140 [114][115][116][117][118][119] pathway and down-regulation of inhibitor of apoptosis proteins (18). Another study reports that matrine inhibits the invasive activities of human osteosarcoma cells through down-regulation of the ERK/NF-κB pathway in intro and in vivo (19).…”
Section: Alkaloidmentioning
confidence: 99%
“…Fomitoside-K, a biologically active component isolated from a mushroom Fomitopsis nigra, also can increase apoptosis of YD-10B human oral squamous cells through the mitochondrial pathway (118). In A549 lung cancer cells, oleifolioside B, a cycloartane-type triterpene glycoside isolated from Dendropanax morbifera Leveille, promotes apoptosis through targeting the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway which can antagonize the NF-κB pathway (119). Periplocin and icariin which were mentioned above also belong to the glycoside family.…”
Section: Glycosidementioning
confidence: 99%